2021
DOI: 10.3390/pharmaceutics13101613
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Amorphous Oral Thin Films Using Solvent-Free Processes: Comparison between 3D Printing and Hot-Melt Extrusion Technologies

Abstract: Conventional oral dosage forms may not always be optimal especially for those patients suffering from dysphasia or difficulty swallowing. Development of suitable oral thin films (OTFs), therefore, can be an excellent alternative to conventional dosage forms for these patient groups. Hence, the main objective of the current investigation is to develop oral thin film (OTF) formulations using novel solvent-free approaches, including additive manufacturing (AM), hot-melt extrusion, and melt casting. AM, popularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…Apart from this, no potential degradation was observed up to 300.78°C, demonstrating the thermal stability of Soluplus ® up to this temperature. Similar TGA data of Soluplus ® was reported previously [82,81]. Further, a continuous weight loss of 21.961% between 300.78°C to 355.183°C, 67.97% between 355.183°C to 464°C, and 7.508% between 464°C to 800°C were due to its degradation.…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 88%
“…Apart from this, no potential degradation was observed up to 300.78°C, demonstrating the thermal stability of Soluplus ® up to this temperature. Similar TGA data of Soluplus ® was reported previously [82,81]. Further, a continuous weight loss of 21.961% between 300.78°C to 355.183°C, 67.97% between 355.183°C to 464°C, and 7.508% between 464°C to 800°C were due to its degradation.…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 88%
“…We found that 3D printing technology has the following applications in pharmacy: To print pills according to the individual condition of the patient [ 118 ]; To make the dosage more suitable for each patient’s own physical condition [ 119 , 120 , 121 , 122 ]; To print tablets with specific shapes and structures to control the release rate [ 123 , 124 ]; To precisely control the distribution within cells [ 125 ]; To develop biomaterials to build organs [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ]; To develop biomaterials to build organs-on-a-chip for drug testing [ 152 ]; To make transdermal microneedle patches to reduce pain in patients [ 153 ]. …”
Section: Discussionmentioning
confidence: 99%
“…The advanced physicochemical analyses, including Raman mapping, revealed the existence of drugs in an amorphous state in both the HME and 3D-printed films. Nevertheless, a relatively consistent distribution of amorphous drugs was observed in the 3D-printed films in comparison to the films fabricated using other techniques [ 116 ]. The findings indicate that combining the HME and 3DP methods holds significant promise for improving the physical attributes of formulations and producing ODFs with favorable features, such as rapid drug dissolution rates.…”
Section: Manufacturing Methodsmentioning
confidence: 97%